Adult Children of Gay and Lesbian Parents: Religion and the Parent-Child Relationship. (May 2013) - Lytle, Megan C.; Foley, Pamela F.; Aster, Amanda M.
Previous scholars have explored various challenges facing children of gay and lesbian individuals, and some have explored the impact of a parent's sexual orientation on the parent-child relationship. However, the impact of religion on the parent-child relationships of adult children with a gay or lesbian parent has been overlooked. In this study, 10 adult children with both a gay or lesbian parent and a heterosexual parent were interviewed and asked to retrospectively explore how religion impacted their parent-child relationships. The following themes emerged from phenomenological analysis of the interviews: (a) family break-up more difficult than the parents' coming out; (b) discovery that parent was gay or lesbian; (c) initial shame over having a gay or lesbian parent; (d) positive aspects of having a gay or lesbian parent; (e) redefined relationship with religion; and (f) impact of culture on how gay and lesbian individuals are viewed.